A framework for cultural heritage management and research: the Cancellara case study. Issue 2 (13th November 2018) - Biscione, Marilisa; Danese, Maria; Masini, Nicola
ABSTRACT: This paper deals with the approach used to create the digital cultural heritage map (hereafter, c.h.) of the mountain village of Cancellara and its territory, located in Basilicata, Southern Italy. The map is thought to be an exhaustive georeferenced catalogue of sites of cultural interest to bring fresh insights and new life to the c.h. and support decisions for their protection, management and valorization by the municipality and public bodies, national and regional, designated to fulfil the duties in ensuring the protection and accessibility of cultural heritage. A digital c.h. map is also important and useful for scholars who conduct studies and investigations as well as for private companies and cultural associations which work in the field of Cultural and Creative Industry. This map allows access to information useful for the reconstruction of the history of the place, dispersed among various private and public archives or unpublished. The map includes a chart at the territory scale, and more detail for the built-up area and its historical centre. It summarises data from heterogeneous sources.